Ligand Taxonomy for Bioinorganic Modeling of Dioxygen‐Activating Non‐Heme Iron Enzymes. Issue 27 (17th March 2020) - Park, Hyunchang; Lee, Dongwhan
Abstract: Novel functions emerge from novel structures. To develop efficient catalytic systems for challenging chemical transformations, chemists often seek inspirations from enzymatic catalysis. A large number of iron complexes supported by nitrogen‐rich multidentate ligands have thus been developed to mimic oxo‐transfer reactivity of dioxygen‐activating metalloenzymes. Such efforts have significantly advanced our understanding of the reaction mechanisms by trapping key intermediates and elucidating their geometric and electronic properties. Critical to the success of this biomimetic approach is the design and synthesis of elaborate ligand systems to balance the thermodynamic stability, structural adaptability, and chemical reactivity. In this Concept article, representative design strategies for biomimetic atom‐transfer chemistry are discussed from the perspectives of "ligand builders". Emphasis is placed on how the primary coordination sphere is constructed, and how it can be elaborated further by rational design for desired functions. Abstract : Designer ligands for biomimetic chemistry : A judicious combination of donor atoms, ligand denticity, and backbone topology dictates the stereochemistry and reactivity of iron complexes to mimic non‐heme enzymes, which reductively activate dioxygen to catalyze oxidative transformations of organic molecules.